Processing and Performance of Polymeric Transparent Conductive Composites - Parul Jain; Ranjani Muralidharan; Jennifer Sedloff; Xiao Li; Norma A. Alcantar; Julie P. Harmon (International Journal of Polymer Science)
Recent advances in microelectronic and optoelectronic industries have spurred interest in the development of reticulate doped polymer films containing “metallic” charge transfer complexes. In this study, such reticulate doped polymer films were prepared by exposing solid solutions of bis(ethylenedioxy) tetrathiafulvalene (BEDO-TTF) in polycarbonate (PC) to iodine, forming conductive charge transfer complexes. The resulting films exhibited room temperature conductivities ranging from 6.33 to  S    cm−1. The colored iodine complexes in the film were reduced by cyclic voltammetry yielding conductive, colorless, transparent films. We were intrigued to examine the dielectric properties of BEDO-TTF in solid solution in PC prior to formation of the charge transfer complex as no such studies appear in the literature. Dielectric analysis (DEA) was used to probe relaxations in neat PC and BEDO-TTF/PC. BEDO-TTF plasticized the PC and decreased the glass transition temperature. Two secondary relaxations appeared in PC films, whereas the transitions merged in the BEDO-TTF/PC film. DEA also evidenced conductivity relaxations above 180°C which are characterized via electric modulus formalism and revealed that BEDO-TTF increased AC conductivity in PC.